O ambiwalentnym humorze Karla Michala - Czernikow, Olga (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The paper tackles the topic of negative and ambivalent humour from Karel Michal’s short story collection Everyday Spooks. Starting from the concepts of humour (present e.g. in theoretical works of Jean-Paul, Baudelaire, and Bachtin) based on the existence of the negative feature, the author examines the functioning of the degrading role of humour in the Czech writer’s debut volume. Carried out with these tools, the analysis of negative strategies in humoristic writings of Michal, allows for an reinterpretation of his early texts and makes it possible to view them as perverse moralities.
On the ambivalent humour of Karel Michal
Keywords: Karel Michal; humour; Czech literature